Management of Anesthesia in Patients with DIC, AKI, and Post-Laparotomy Hypoglycemia due to Diffuse Peritonitis and Sepsis - Sakti, Matdhika; Syaifuly, Irfan; Aulia, Nursofi (Jurnal KESANS : Kesehatan dan Sains, 2025)
This case report describes the management of anesthesia in patients with disseminated intravascular coagulation (DIC), acute kidney injury (AKI), and hypoglycemia after undergoing laparotomy due to diffuse peritonitis and sepsis. The 61-year-old male patient initially came in with acute abdominal pain and underwent an appendectomy, but his clinical condition soon worsened. The study highlights perioperative and clinical decision-making challenges related to airway management, fluid resuscitation, and intensive care. Emphasis is placed on the importance for anesthesia practitioners to recognize sepsis-related complications early.